UniCAR T cell immunotherapy enables efficient elimination of radioresistant cancer cells. (1st January 2020) - Arndt, Claudia; Loureiro, Liliana R.; Feldmann, Anja; Jureczek, Justyna; Bergmann, Ralf; Máthé, Domokos; Hegedüs, Nikolett; Berndt, Nicole; Koristka, Stefanie; Mitwasi, Nicola; Fasslrinner, Frederick; Lamprecht, Chris; et al.
ABSTRACT: Induction or selection of radioresistant cancer (stem) cells following standard radiotherapy is presumably one of the major causes for recurrence of metastatic disease. One possibility to prevent tumor relapse is the application of targeted immunotherapies including, e.g., chimeric antigen receptor (CAR) T cells. In light of long-term remissions, it is highly relevant to clarify whether radioresistant cancer cells are susceptible to CAR T cell-mediated killing. To answer this question, we evaluated the anti-tumor activity of the switchable universal chimeric antigen receptor (UniCAR) system against highly radioresistant head and neck squamous cell carcinoma cells both in vitro and in vivo . Following specific UniCAR T cell engagement via EGFR or CD98 target modules, T cell effector mechanisms were induced including secretion of pro-inflammatory cytokines, up-regulation of granzyme B and perforin, as well as T cell proliferation. CD98- or EGFR-redirected UniCAR T cells further possess the capability to efficiently lyse radioresistant tumor cells. Observed anti-tumor effects were comparable to those against the radiosensitive parental cell lines. Finally, redirected UniCAR T cells significantly inhibited the growth of radioresistant cancer cells in immunodeficient mice. Taken together, our obtained data underline that the UniCAR system is able to overcome radioresistance. Thus, it represents an attractive technology for the development of combined radioimmunotherapeutic approaches that might improve the outcome of patients with metastatic radioresistant tumor diseases.